Relationship between Skeletal Maturity Indicators and Dental Calcification Stages in a Sample Pediatric Population - Akshaya Ojha; Riddhi Chawla; Tarun Sihag; Ameena Ahmed; Ahtesham A. Qurishi; Laleena Rajkumari (Indian Journal of Dental Research)
Context: Human growth shows considerable variation. In addition to constitutional differences in the timing of maturation, there are diseases, systemic disorders and environmental factors that may affect a child's physiologic maturity. Interrelationships among skeletal, somatic and sexual maturity have been shown to be consistently strong. The study was conducted to evaluate the relationship between dental calcification stages and skeletal maturity indicators. Materials and Methods: The hand wrist radiographs, the lateral cephalogram and the orthopantomogram (OPG) of 120 patients (60 males and 60 females, age group 8–14 years) were taken. The hand wrist radiographs were analyzed using Fishman's skeletal maturity index (SMI), and the cephalograms analyzed by cervical vertebrae maturation (CVM) by Baccetti. OPG was analyzed according to the Demirjian's system. Result: On assessment, cervical vertebrae maturation indicator (CVMI) staging showed significant results with a correlation coefficient of 0.716 being the highest in canines in males while assessment of dental calcification stages and its comparison with skeletal maturity indicator showed insignificant results. The correlation coefficient values were 0.11, 0.09, 0.09 and 0.13 for canine, first premolar, second premolar and second molar respectively. Conclusion: There is a strong correlation between the maturation stage of cervical vertebrae and calcification stages of canine, first premolar, second premolar and second molar as determined by Demirjian's method.